Voluntary simplicity in Turkey: a segmentation approach - Karapınar, Ekin (My University, 2013)
TÜRKİYE’DE GÖNÜLLÜ SADELİK: BİR SEGMENTASYON YAKLAŞIMI ÖZET Günümüzün en büyük sorunlardan biri tüketimin yüksek seviyede olmasıdır. Birçok birey aşırı tüketimin çevre ve insanlar için olumsuz sonuçlar yaratacağı endişesi içindedir. Bu nedenle, bireyler anti-materyalizm ve ruhsal sağlık konularıyla daha fazla ilgilenmeye başlamışlardır. “Gönüllü Sadelik” yaşam tarzı ise maddesel sadelik, kendi kendine yetme ve çevreye duyarlı bir yaşama derinlemesine bağlıdır. Bu çalışmanın amacı, Türkiye’de yaşayan gönüllü sade yaşam tarzını benimseyen bireyler hakkında bir inceleme yapmaktır. Ayrıca, bu çalışma bireyleri benzer özelliklere sahip gruplara ayırmayı ve oluşturulan grupların demografik görünümlerini belirlemeyi amaçlamaktadır. Anketi 819 denek yanıtlamıştır. Veriler, olasılıksal olmayan kolaydan örnekleme metodu kullanılarak elde edilmiştir. Çalışmada, IBM SPSS Statistics 20 kullanılarak, faktör analizi ve kümeleme analizi yapılmıştır. Sadelik, Gönüllü Sade Tüketici, Pazarlama, Kümeleme Analizi, Tipoloji VOLUNTARY SIMPLICITY IN TURKEY: A SEGMENTATION APPROACH

Nowadays, high level of consumption is an important problem. Due to the possible consequences of overconsumption, many individuals are concerned about the environment and people. Therefore, individuals become more interested in non-materialism and spiritual well-being. “Voluntary Simplicity” lifestyle is highly linked to material simplicity, self-sufficiency, and environmentally conscious living. The aim of the study is to provide an examination of voluntary simplifiers in Turkey. In addition, the study aims to segment voluntary simplifiers into groups with similar characteristics and to determine demographic profiles of cluster. The data were collected from a sample of 819 respondents by using non-probabilistic convenience sampling method. Given this aim, Factor Analysis and then Cluster Analysis were conducted using IBM SPSS Statistics 20. Voluntary Simplicity, Voluntary Simplicity Consumer, Marketing, Cluster Analysis, Typology
Keywords: Pazarlama; Üretim Yönetimi